Cloud computing technology: Reducing carbon footprint in beef supply chain - Singh, Akshit; Mishra, Nishikant; Ali, Syed Imran; Shukla, Nagesh; Shankar, Ravi (International journal of production economics, 2015)
Global warming is an alarming issue for the whole humanity. The manufacturing and food supply chains are contributing significantly to the large-scale carbon emissions. Beef supply chain is one of the segments of food industry having considerable carbon footprint throughout its supply chain. The major emissions are occurring at beef farms in the form of methane and nitrous oxide gases. The other carbon hotspots in beef supply chain are abattoir, processor, logistics and retailer. There is a huge amount of pressure from government authorities to all the business firms to cut down carbon emissions. The different stakeholders of beef supply chain especially small and medium-sized stakeholders, lack in technical and financial resources to optimize and measure carbon emissions at their end. There is no integrated system which can address this issue for the entire beef supply chain. Keeping the same in mind, in this paper, an integrated system is proposed using Cloud Computing Technology (CCT) where all stakeholders of beef supply chain can minimize and measure carbon emission at their end within reasonable expenses and infrastructure. The integrated approach of mapping the entire beef supply chain by a single cloud will also improve the coordination among its stakeholders. The system boundary of this study will be from beef farms to the retailer involving logistics, abattoir and processor in between. The efficacy of the proposed system is demonstrated in a simulated case study.